2011
DOI: 10.3354/meps09049
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of soluble extracellular polymeric ­substances and transparent exopolymer particle pools in coastal ecosystems

Abstract: Time series of soluble extracellular polymeric substance (S-EPS) and transparent exopolymer particle (TEP) fractions, as well as biological, physical and chemical parameters, were studied in natural phytoplankton assemblages at 2 macrotidal sites located in the English Channel for 3 yr. The first site, the Bay des Veys (BDV), is sheltered from prevailing winds and influenced by a high river discharge, whereas the second, Lingreville-sur Mer (LGV), is exposed to the open ocean and to dominant winds. At both sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
26
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 67 publications
(102 reference statements)
10
26
2
Order By: Relevance
“…The TEP concentrations that we measured across the OAO (CU included) generally fall within the range reported in other studies from the open ocean (Table 2). However, our levels are higher than those observed in the Mediterranean Sea , Pacific Ocean (Ramaiah et al, 2005;Kodama et al, 2014;Iuculano et al, 2017b) and one study in the northwestern Atlantic Ocean (Cisternas-Novoa et al, 2015), and lower than that reported in the eastern Mediterranean Sea (Bar-Zeev et al, 2011). We believe that one of the reasons for the higher values found in our study compared with these previous studies is the depth.…”
Section: Teps Across the Surface Atlantic Oceancontrasting
confidence: 87%
“…The TEP concentrations that we measured across the OAO (CU included) generally fall within the range reported in other studies from the open ocean (Table 2). However, our levels are higher than those observed in the Mediterranean Sea , Pacific Ocean (Ramaiah et al, 2005;Kodama et al, 2014;Iuculano et al, 2017b) and one study in the northwestern Atlantic Ocean (Cisternas-Novoa et al, 2015), and lower than that reported in the eastern Mediterranean Sea (Bar-Zeev et al, 2011). We believe that one of the reasons for the higher values found in our study compared with these previous studies is the depth.…”
Section: Teps Across the Surface Atlantic Oceancontrasting
confidence: 87%
“…The present fluctuations in the cell carbohydrate contents (fmol C [glucose equivalent] cell −1 ) will be discussed in re gard to the total carbon and nitrogen cell content of Crocosphaera watsonii (fmol C cell −1 and fmol N cell −1 ) described by Dron et al (2012). The soluble EPS fraction (< 0.2 µm) is an extracellular carbohydrate fraction released by cells, dissolved in water (Underwood et al 1995, Klein et al 2011; the fraction is obtained after filtration of the culture through a 0.2 µm polycarbonate filter to discard the cells. Two distinct pools of soluble EPS that were present in the filtrate were identified according to their molecular weight: LMW and HMW (Underwood et al 1995(Underwood et al , 2004.…”
Section: Total Cellular Carbohydrate Cellular Carbohydrate Pools Andmentioning
confidence: 99%
“…EPS show various forms that can be free or strongly attached to cells (Passow 2002). Most EPS are found in the free fraction, constituted by (1) low and high molecular weight soluble EPS (LMW soluble EPS and HMW soluble EPS, respectively) (Underwood et al 1995, 2004, Klein et al 2011 and (2) a particulate fraction (Thornton 2002) called transparent exopolymeric particles (TEP) (Alldredge et al 1993). EPS are excreted by numerous phytoplanktonic organisms and bacteria (Myklestad 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A duplicate standard curve using xanthan gum was used to determine the concentration of TEP following Claquin et al [22]. First, triplicates at T initial and of the feed tank water from the cross-flow system at T 7d (10 mL) were filtered using a 0.4 μm polycarbonate filter under gentle vacuum and then transferred into 0.2 μm filtered raw seawater (5 mL) and stored at −20°C, as described by Klein et al [23]. Samples were then analyzed following Balzano et al [24].…”
Section: Tep Colorimetric Quantificationmentioning
confidence: 99%